Aquaculture Nutrition 2014
DOI: 10.1002/9781118897263.ch11
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Applications in Crustaceans

Abstract: Crustacean aquaculture, and more specifically shrimp culture, faces several challenges in order to increase production yield while maintaining sustainability. The various disease outbreaks that have been continuously affecting the sector for almost two decades, together with the increasing demand for environmentally friendly aquaculture and the pressure from customers for safe and traceable products, are fundamentally modifying the culture practices of shrimp and other crustacean species. It is today well acce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 149 publications
2
6
0
Order By: Relevance
“…The major purpose of dietary prebiotic and probiotic application in crustacean's aquaculture is elevation of beneficial LAB bacteria, which are not dominant parts of crustacean intestinal microbiota [84,85]. Interestingly, the results from 97 days of feeding in the present study well exhibited that combination of GOS and L. plantarum through diet could beneficially modulate P. leptodactylus intestinal microbiota via growth of LAB bacteria.…”
Section: Discussionsupporting
confidence: 59%
“…The major purpose of dietary prebiotic and probiotic application in crustacean's aquaculture is elevation of beneficial LAB bacteria, which are not dominant parts of crustacean intestinal microbiota [84,85]. Interestingly, the results from 97 days of feeding in the present study well exhibited that combination of GOS and L. plantarum through diet could beneficially modulate P. leptodactylus intestinal microbiota via growth of LAB bacteria.…”
Section: Discussionsupporting
confidence: 59%
“…To avoid overlap with previous reviews, we have focused on the papers published from 2014. Readers with special interests on previous studies, are referred to the reviews of Ringø and Gatesoupe ( 1998 ), Nayak ( 2010 ), Carnevali et al ( 2014 ), Castex et al ( 2014 ), De et al ( 2014 ), Lauzon et al ( 2014 ), Merrifield et al ( 2014 ), Ringø et al ( 2014 ) and Hoseinifar et al ( 2016c ).…”
Section: Lab As Probioticmentioning
confidence: 99%
“…Probiotics are defined as live microorganisms which confer a health benefit on the host, when supplemented in adequate amounts (FAO/WHO ), as dietary supplementations of probiotics to aquatic animals have shown promising results (Balcazar, ; Carnevali, Sun, Merrifield, Zhou, & Picchietti, ; Castex, Daniels, & Chim, ; Gatesoupe, Ronald Ross, & Victor, ; Lauzon, Dimitroglou, Merrifield, Ringo, & Davies, ; Merrifield & Carnevali, ). Furthermore, previous studies have reported that dietary probiotics effectively improved the feed utilization, modulated intestinal microflora, enhanced the immunity and also improved the antagonism to pathogens (Balcázar et al., ; Irianto & Austin, ; Kesarcodi‐Watson, Kaspar, Lategan, & Gibson, ; Merrifield et al., ; Nayak, ).…”
Section: Introductionmentioning
confidence: 99%